Tinjauan Yuridis Pertanggungjawaban Pemegang Saham Selaku Direktur Dalam Perseroan Perorangan Terhadap Putusan Pernyataan Kepailitan - Fiona Chrisanta; Harahap, Rahil Sasia Putri (Fakultas Hukum Universitas Primagraha, 2023)
Incorporated Individual (PP) is a legal entity that can be established by 1 (one) founder who also acts as shareholder and director. PP was introduced to the public when the Job Creation Law was enacted in 2021. However, in practice there are still many questions and legal vacuums, especially regarding the position and process of bankruptcy. This study aims to review and evaluate regulations regarding the accountability of Shareholders as Directors in Incorporated Individual Against Bankruptcy Declaration Decisions. The approach method used in this research is normative juridical. The results to be aimed at are knowing the responsibility of shareholders as directors of individual companies against bankruptcy and knowing what needs to be evaluated regarding regulations regarding Incorporated Individual.